Endoscopic retrieval of Pendastomid worm occlusion in a rescued Indian Rat Snake (Ptyas mucosa) - Veeraselvam; Selvaraj P; Yogeshpriya , S; Saravanan, M; Jayalakshmi, E; Tamileniyan, E (Indian Journal of Veterinary Medicine, 2025)
A rat snake was presented with the history of rescue from a rural household. It was said to have some hit injury and was dull and reluctant to move. Bubbling of nasal discharge from the nostril, open mouth breathing and copious salivation were noticed. On auscultation deep breathing was observed; respiratory distress was noticed. The snake was medicated with ketamine hydrochloride and Diazepam and prepared for endoscopic assessment. A 2.8mm thin flexible endoscopy was used to assess the trachea, lungs and air sac area. In the middle of respiratory tract, occlusion with Pentastomid worm was noticed which was retrieved using grasping forceps. Dextrose Normal Saline was administered orally using feeding tubes and ivermectin was given subcutaneously. The snake recovered uneventfully after endoscopy and later rehabilitated and released in to a non-human habitat area.